Development and content validation of the percutaneous nephrolithotomy assessment score. (5th August 2020) - Quirke, Kate; Aydın, Abdullatif; Bultitude, Matthew; Sarıca, Kemal; Glass, Jonathan; Khan, Azhar; Marsh, Howard; Al‐Hayek, Samih; Wiseman, Oliver; Patterson, Jake; Makanjuola, Jonathan; Skolarikos, Andreas; et al.
Abstract : Objectives: To develop and content validate a percutaneous nephrolithotomy assessment score, taking into consideration the procedure‐specific risks. Methods: This prospective international study utilized the Healthcare Failure Mode and Effect Analysis to systematically outline percutaneous nephrolithotomy and failure modes for each step. A total of 25 h was spent observing percutaneous nephrolithotomy carried out by six expert surgeons. Hazard analysis scoring was carried out by 11 experts. It was determined if the steps were single point weaknesses. Single point weaknesses and those assigned a hazard score ≥4 were included in the percutaneous nephrolithotomy assessment score. The tool was then content validated by 16 experts from 10 countries. Results: Application of the Healthcare Failure Mode and Effect Analysis identified 64 failure modes; 37 failure modes had a hazard score ≥4. After adaptations based on expert feedback the final percutaneous nephrolithotomy assessment score was developed containing 10 phases, 21 processes and 47 subprocesses. All participants agreed that the tool contained pertinent procedural steps. Conclusions: This study has developed and shown the international content validity of a novel percutaneous nephrolithotomy assessment score. The tool can be utilized in modular operating room training to quantify operator progress, and can be used in conjunction with other modules as part of a complete percutaneous nephrolithotomy curriculum for trainees.